Pain and physical condition during pregnancy and post-partum period in inactive women during pregnancy - ضويا رشا (Latakia University Journal -Medical Sciences Series, 2023)
Physical activity during pregnancy and in post-partum period is one of the modern topics in European countries and the Arab community. Nevertheless, we find a lot of scientific research that study the effect of exercise on a woman’s body and her fetus during pregnancy. All of these studies agreed on the safety of exercise during pregnancy, showing its benefit to the woman’s against the biomechanical and physiological changes that occur in her body during this period. This study aims to show the most important biomechanical and physiological changes that occur in the woman’s body, not only at the end of pregnancy, but even until the fourth month in post-partum period, in the absence of sports activity in this period. The results showed, after comparing active women before pregnancy and inactive women before pregnancy, that not practicing sports activities during pregnancy leads to a negative impact on the mechanics of the trunk region, and thus the emergence of pain in this region, which in turn leads to a negative impact on health. And that extends to 2-4 months in post-partum period. This study also showed that the effect of these pains on the active women before pregnancy and those who were not active before pregnancy was similar in terms of intensity and location in the absence of sports activity during pregnancy.